Assessment of Groundwater Quality in Anantnag District of Kashmir Valley (International Journal of Innovative Research in Engineering & Management, 2023)
Groundwater plays a vital role in meeting  the domestic, agricultural, and industrial water demands in  the Anantnag district of Kashmir. However, the rapid  urbanization, industrialization, and agricultural practices  have raised concerns regarding the quality of groundwater in  the region. This study aims to assess the groundwater quality  in Anantnag, Kashmir, by evaluating key physicochemical  parameters and determining the presence of potential  contaminants. To achieve the objectives, a systematic sampling campaign  was conducted across various locations in Anantnag district.  Groundwater samples were collected from representative  wells, tube wells, and hand pumps. A comprehensive  analysis was carried out to determine the physicochemical  parameters including pH, electrical conductivity (EC), total  dissolved solids (TDS), and concentrations of major ions  such as chloride (Cl-), nitrate (NO3-), sulfate (SO42-), and  fluoride (F-). The results of the groundwater analysis  revealed significant variations in physicochemical parameters  across different sampling locations. The pH levels ranged  from acidic to alkaline, with certain areas exhibiting values  beyond the acceptable range. Elevated levels of TDS and EC  were observed in specific locations, indicating potential  contamination sources. The concentrations of chloride,  nitrate, sulfate, and fluoride were also found to exceed the  permissible limits in some areas, suggesting contamination  from anthropogenic activities such as agricultural runoff,  industrial discharges, and improper waste management. Furthermore, statistical analysis techniques were employed to  assess the correlation between different parameters and to  identify potential sources of contamination. Geographical  Information System (GIS) mapping was utilized to visualize  the spatial distribution of groundwater quality parameters,  facilitating the identification of high-risk areas. The findings  of this study provide critical insights into the current state of  groundwater quality in Anantnag, Kashmir, highlighting  areas that require immediate attention for remediation and  management. The results can serve as a valuable reference  for policymakers, water resource managers, and other  stakeholders to implement appropriate measures for the  protection and sustainable use of groundwater resources in  the region. Additionally, this study emphasizes the  importance of continuous monitoring and periodic  assessments to ensure the long-term availability of safe and  potable groundwater in Anantnag, Kashmir.
Keywords: Groundwater; pH value; contamination; polluted; TDS; Chloride and Nitrate